AQUATIC INSECT COMMUNITIES IN SEVERAL WATERFALLS OF MOUNT HALIMUN SALAK AND BABAKAN MADANG : AQUATIC INSECT COMMUNITIES IN SEVERAL WATERFALLS OF MOUNT HALIMUN SALAK AND BABAKAN MADANG - Muhammad Zaki Abdullah; Windra Priawandiputra; Taruni Sri Prawasti (Departemen Biologi, Institut Pertanian Bogor, 2026)
Waterfalls in Mount Halimun Salak and Babakan Madang serve as critical water sources for Bogor residents, necessitating environmental monitoring using aquatic insect bioindicators. This study identified and compared aquatic insect communities across these waterfalls to assess water quality. EPT orders (Ephemeroptera, Plecoptera, Trichoptera) were prioritized as bioindicators due to their sensitivity to physicochemical changes and association with clean water. Purposive sampling was conducted along 10-meter transects at three stations per location with three replications. Samples were collected using hand nets and preserved in 70% alcohol. Environmental parameters measured included humidity, water temperature, TDS, current velocity, and pH. Specimens were identified using stereo microscopes, reference materials, and the Waterbug Application. Data analysis employed Shannon-Wiener Diversity Index, EPT abundance metrics, NMDS ordination, and BMWP-ASPT Index. Results revealed higher individual counts at Babakan Madang, while Mount Halimun Salak demonstrated greater species diversity. The abundance of EPT is dominated by the Baetidae Family. NMDS Ordination shows the distribution of families in 6 observation stations. Based on the measurement of the BMWP-ASPT Index, the Mount Halimun Salak and Babakan Madang waterfalls have moderately polluted water quality. These findings highlight the importance of continued biomonitoring to protect these vital freshwater resources for local communities.